The Challenge of Biblical Textual Criticism: The Case of the Dutch Edition of the Septuagint (1709) - Ana Catană-Spenchiu; Constantin Răchită (Religions, 2022)
An overview of the main European biblical tradition of the Septuagint shows that much work has been carried out in this field of research. Prominent scholars investigated the Old Testament from a thematic diversity point of view, from the history of the text and its contextualization to a variety of translation topics. We investigate, in this article, a lesser-known edition of the Septuagint from the early 18th Century, edited by Lambert Bos and printed in Franeker. Lambert Bos’ biblical philology fits into the patterns of Dutch textual philology, consolidated in the 17th century and built on the solid foundations provided by the grammatical and lexical analysis of ancient texts. A deeper understanding of the issues raised by the texts’ transmission opens a new field of research which admits that a true appreciation of the texts’ content must be preceded by their recovery in as ‘authentic’ a form as possible. The present article aims to restore the image of a Dutch Hellenist of pre-modern philology, and to present important data on his key works, highlighting the defining characteristics of the Franeker edition (1709) of the Septuagint with an analysis from a modern perspective of the principles and methods he followed in the actual practice of biblical textual criticism.